Synthesis of fluorinated δ-lactams via cycloisomerization of gem-difluoropropargyl amides - Arimitsu, Satoru; Hammond, Gerald B. (Beilstein Journal of Organic Chemistry, 2010)
gem-Difluoro-1,7-enyne amides are suitable building blocks for the synthesis of difluorodihydropyridinones via a ring-closing metathesis reaction, and of 4,4-difluoro-3-oxoisoquinolines through a ring-closing metathesis–enyne metathesis tandem reaction. These products, in turn, undergo a Diels–Alder reaction to yield heterotricyclic systems in moderate to good yields.
Keywords: bicyclic lactams; cycloisomerization; difluoropropargyl; enyne; ring-closing metathesis

(untitled) - Ghose, A. K.; Viswanadhan, V. N.; Wendoloski, J. J. (J. Comb. Chem., 1999)

(untitled) - Wakselman, M.; Joyeau, R.; Kobaiter, R.; Boggetto, N.; Vergely, I.; Maillard, J.; Okochi, V.; Montagne, J.-J.; Reboud-Ravaux, M. (FEBS Lett., 1991)

(untitled) - Maillard, J.-L.; Favreau, C.; Reboud-Ravaux, M.; Kobaiter, R.; Joyeau, R.; Wakselman, M. (Eur. J. Cell Biol., 1990)

(untitled) - Joyeau, R.; Molines, H.; Labia, R.; Wakselman, M. (J. Med. Chem., 1988)

(untitled) - Angelastro, M. R.; Bey, P.; Mehdi, S.; Peet, N. P. (Bioorg. Med. Chem. Lett., 1992)

(untitled) - Evans, G. B.; Furneaux, R. H.; Lewandowicz, A.; Schramm, V. L.; Tyler, P. C. (J. Med. Chem., 2003)

(untitled) - Inagaki, H.; Miyauchi, S.; Miyauchi, R. N.; Kawato, H. C.; Ohki, H.; Matsuhashi, N.; Kawakami, K.; Takahashi, H.; Takemura, M. (J. Med. Chem., 2003)

(untitled) - Thaisrivongs, S.; Pals, D. T.; Kati, W. M.; Turner, S. R.; Thomasco, L. M.; Watt, W. (J. Med. Chem., 1986)

(untitled) - Fustero, S.; Bello, P.; Fernández, B.; del Pozo, C.; Hammond, G. B. (J. Org. Chem., 2009)

Fluorinated Heterocycles - Hammond, G. B.; Arimitsu, S. (Synthesis of gem-difluorinated heterocycles using a difluoropropargyl building block, 2009)

(untitled) - Arimitsu, S.; Bottom, R. L.; Hammond, G. B. (J. Fluorine Chem., 2008)

(untitled) - Arimitsu, S.; Fernández, B.; del Pozo, C.; Fustero, S.; Hammond, G. B. (J. Org. Chem., 2008)

(untitled) - Fustero, S.; Fernández, B.; Bello, P.; del Pozo, C.; Arimitsu, S.; Hammond, G. B. (Org. Lett., 2007)

(untitled) - Fustero, S.; Sánchez-Roselló, M.; Jiménez, D.; Sanz-Cervera, J. F.; del Pozo, C.; Aceña, J. L. (J. Org. Chem., 2006)

(untitled) - Deiters, A.; Martin, S. F. (Chem. Rev., 2004)
(see for a review)

(untitled) - Cheng, Z.-L.; Chen, Q.-Y. (J. Fluorine Chem., 2006)

(untitled) - Wang, R.-W.; Qing, F.-L. (Org. Lett., 2005)

(untitled) - Pan, Y.; Holmes, C. P.; Tumelty, D. (J. Org. Chem., 2005)

(untitled) - Beeler, A. B.; Gadepalli, R. S. V. S.; Steyn, S.; Castagnoli, N., Jr; Rimoldi, J. M. (Bioorg. Med. Chem., 2003)

(untitled) - Poulsen, C. S.; Madsen, R. (Synthesis, 2003)

(untitled) - Mori, M.; Sakakibara, N.; Kinoshita, A. (J. Org. Chem., 1998)

(untitled) - Hong, S. K.; Sanders, D. P.; Lee, C. W.; Grubbs, R. H. (J. Am. Chem. Soc., 2005)

(untitled) - Dabideen, D. R.; Cheng, K. F.; Aljabari, B.; Miller, E. J.; Pavlov, V. A.; Al-Abed, Y. (J. Med. Chem., 2007)

(untitled) - Mewshaw, R. E.; Bowen, S. M.; Harris, H. A.; Xu, Z. B.; Manas, E. S.; Cohn, S. T. (Bioorg. Med. Chem. Lett., 2007)

(untitled) - Mewshaw, R. E.; Edsall, R. J., Jr; Yang, C.; Manas, E. S.; Xu, Z. B.; Henderson, R. A.; Keith, J. C., Jr; Harris, H. A. (J. Med. Chem., 2005)

(untitled) - Trost, B. M.; Toste, F. D.; Pinkerton, A. B. (Chem. Rev., 2001)

(untitled) - Naota, T.; Takaya, H.; Murahashi, S.-I. (Chem. Rev., 1998)

(untitled) - Lee, H.-Y.; Kim, H. Y.; Tae, H.; Kim, B. G.; Lee, J. (Org. Lett., 2003)
(a similar approach with non-fluorinated building blocks has been reported)